Determinants of Tax Compliance among Small and Medium Enterprises: An Empirical Study in Indonesia - Loso Judijanto; Willy Nurhayadi; Eko Cahyo Mayndarto; Ahalik Ahalik; Eri Kristanto; Eko Sudarmanto (Westscience Press, 2026)
This study investigates the factors influencing tax compliance among Small and Medium-Sized Enterprises (SMEs) in Indonesia. Using a quantitative approach, data were collected from 150 SME owners and managers through a structured survey with Likert-scale questions. The study examines the impact of tax knowledge, tax attitudes, administrative burdens, business size, and financial constraints on tax compliance. Data analysis was performed using SPSS version 25, employing descriptive statistics, correlation analysis, and multiple regression analysis. The results reveal that tax knowledge and positive tax attitudes are the strongest predictors of tax compliance, while administrative burdens and financial constraints negatively affect compliance. The study highlights the need for improved tax education and simplified tax procedures to increase compliance rates among SMEs. The findings offer valuable insights for policymakers aiming to design more effective tax policies and strategies to encourage higher tax compliance in the SME sector of Indonesia.